The Evolution of Islamic Diplomacy in the Modern Era And its Implications for Global Governance and International Relations - Thaddeus T. Ityonzughul; Nyenye Nwayin Dorine Laure (Universitas Medan Area, 2026)
This study investigates the evolution of Islamic diplomacy in the modern era and its implications for global governance and international relations. It notes the increasing influence of Muslim-majority countries in global affairs, signifying a paradigm shift where Islamic values—such as justice, equality, and compassion—are integrated into diplomatic practices. Utilizing a qualitative methodology grounded in Constructivism and Realism, the research analyzes how ideas, norms, and power dynamics influence state behavior. Data was collected through an extensive literature review and examination of primary religious texts (Quran and Hadith), alongside institutional documents from organizations like the Organization of Islamic Cooperation (OIC) and the Islamic Development Bank (IDB). The findings highlight significant transformations in Islamic diplomacy, tracing its evolution from historical treaties like the Treaty of Hudaybiyah to contemporary multilateral engagement in international organizations. Key modern trends are identified, including a shift toward economic diplomacy, enhanced South-South cooperation, and collaborative efforts in counter-terrorism. While Islamic diplomacy presents opportunities for promoting cultural dialogue, good governance, and addressing global challenges such as climate change and poverty, it also confronts several challenges. These encompass value disparities with Western nations, the destabilizing influence of extremist groups, and the complexities of asymmetrical power dynamics in an anarchic international system. The study concludes that Islamic diplomacy is a crucial element of modern international relations, with the potential to foster a more inclusive, equitable, and peaceful world order. It advocates for open dialogue between Western nations and Muslim-majority countries, encourages Track II diplomacy, and suggests the adoption of nuanced, country-specific strategies to build mutual trust and enhance global stability.